Deciphering the carbon starvation response in Arabidopsis thaliana: autophagy, alternative respiration and beyond - Barros, Jessica Aline Sousa (2020)
Throughout their life, plants are constantly challenged with environmental changes that compromises carbohydrate production. Energy deprivation triggers massive reprogramming of transcription, which further supports cellular energetic homeostasis. Therefore, catabolic pathways are generally activated leading to the catabolism of protein, lipid, and chlorophyll. Although our current understanding of plant mechanisms to overcome low energy conditions has significantly enhanced, there are still many open questions to be addressed. This thesis is therefore largely focused on understanding (i) the importance of autophagy as a mechanism of lipids and chloroplast recycling; and (ii) the transcriptional regulation of respiratory alternative pathways during low energy stress. Compelling evidence demonstrated that autophagy and amino acid catabolism are important factors of plant response to energy deprivation. This fact aside, the importance of autophagy on the remobilization of lipid substrates to sustain energy production remains unclear. Thus, we first summarized and discussed novel findings demonstrating the multifaceted roles of autophagy in lipid metabolism. Next, we provided experimental evidence of autophagy requirement to ensure lipid homeostasis during energy starvation conditions. Our findings revealed that autophagy disruption affects proper membrane mobilization and activates a general chloroplast lipid degradation program while failing to produce cytosolic lipid droplets. The degradation of chloroplasts is a hallmark of natural and stress-induced senescence, and a key role of autophagy in this process has been demonstrated elsewhere. Notably, the marked degradation of chloroplast components in mutants with disruption of autophagy (atg mutants) reported by several previous studies, raised the question whether other pathways of chloroplast degradation may also have a role in the remobilization of chloroplast components. It has been previously reported that the chloroplast vesiculation (CV) pathway is highly induced in atg mutants contributing with their early senescence phenotype during energy starvation. Thus, in the second part of this thesis the importance of CV and its coordination with autophagy under extended darkness was investigated. By using CV RNAi lines it was demonstrated that CV pathway plays a relatively minor role on Arabidopsis starvation response. However, further characterization of double mutants for CV and autophagy pathways highlighted the requirement of CV for chloroplast remodeling of atg mutants under darkness. Within the last chapter novel insights concerning the regulatory components that modulates plant survival under low energetic conditions are shown. To this end, the WRKY45 transcription factor was identified as a potential regulator of metabolic reprogramming, by precisely adjusting amino acid and organic acid response via a possible regulation of mitochondrial stress signaling components. Collectively, the results obtained here describe novel mechanisms underlying plant responses to low energy conditions. These findings are discussed in the context of our current knowledge concerning energetic metabolism, autophagy, and senescence in plants. Keywords: Autophagy. Energetic stress. Lipids. Metabolism. Senescence.